[Alfréd Ruby 10]
Balaton Silver-coast, sleeping in the afternon, Balatonszárszó playing ping-pong, Balatonzamárdi camping, long cue at the Szántód ferry, Dombóvár, Kaposvár, Sárvár, Biatorbágy, Tata the dry lake-bed, Vértesszöllős "Samu" the caveman, Vácrátót botanical garden, Fót , Danube-bend, 1972 open-air bath "bath-life", "langosh" 3 Ft (=HUF), funny cartoon about gymnastc, Solymár lime burning, sailplains, Esztergom, Budapest monuments, Balatonalmádi hotel Auróra, arrive with trabant luggages from the boot, the wiew from 10th floor